2010
DOI: 10.3109/09513590.2010.534612
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptives and endometriosis/adenomyosis

Abstract: Over the past 50 years hormonal contraceptives have gradually developed to be cost-effective medical treatment modalities for primary and secondary therapy of endometriosis/adenomyosis. This is particularly true for the various estrogen/ progestogen combinations as monophasic -particularly progestogen-dominant -preparations in cyclic, long-cyclic and continuous treatment forms. An alternative is the progestogen-only therapy used continuously. Therapeutic effects have been shown for peritoneal, ovarian and deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…15 To decrease the impact of lifestyle on surgery, hormonal therapy had been used for the treatment of AWE, but the use of progestogens, oral contraceptive pills and danazol are not effective because medical treatment gives only partial relief. 16 In addition, the high risk recurrence rate after cessation therapy reported in the previous literature was 4.3-9.1% and the operations were performed again in 10-year follow-up period. 17,18 The limitations of this study are as follows.…”
Section: Discussionmentioning
confidence: 93%
“…15 To decrease the impact of lifestyle on surgery, hormonal therapy had been used for the treatment of AWE, but the use of progestogens, oral contraceptive pills and danazol are not effective because medical treatment gives only partial relief. 16 In addition, the high risk recurrence rate after cessation therapy reported in the previous literature was 4.3-9.1% and the operations were performed again in 10-year follow-up period. 17,18 The limitations of this study are as follows.…”
Section: Discussionmentioning
confidence: 93%
“…No well conducted randomized controlled trials are reported on the pharmacological treatment of adenomyosis using COCs. Patients with dysmenorrhea and menorrhagia may benefit from the resulting amenorrhea, which may provide relief of symptoms (88). The off-label use of COCs for adenomyosis-related symptoms enables satisfactory long-term pain control similar to other drugs, but they are less expensive, with the possibility to be used for longer periods of time (89).…”
Section: Current Medical Treatmentsmentioning
confidence: 99%
“…Hormonal medications to treat symptoms of adenomyosis include combined oral contraceptives, various progestogen‐only medications, and gonadotropin‐releasing hormone agonists. Combined oral contraceptives effectively treat menorrhagia and dysmenorrhea by maintaining a thinner endometrium, which decreases inflammation by blocking cyclooxygenase (Cox‐2) expression 35,36 . However, a recent review concluded that the evidence for treating adenomyosis specifically with combined oral contraceptives is mixed, and some anecdotal reports suggest that combined oral contraceptives may actually stimulate adenomyotic foci in undesirable ways 34 .…”
Section: Developing a Treatment Planmentioning
confidence: 99%
“…Combined oral contraceptives effectively treat menorrhagia and dysmenorrhea by maintaining a thinner endometrium, which decreases inflammation by blocking cyclooxygenase (Cox-2) expression. 35,36 However, a recent review concluded that the evidence for treating adenomyosis specifically with combined oral contraceptives is mixed, and some anecdotal reports suggest that combined oral contraceptives may actually stimulate adenomyotic foci in undesirable ways. 34 Thus, the response to combined oral contraceptives should be monitored carefully.…”
Section: Oral Hormonal Treatmentsmentioning
confidence: 99%